Mechanical properties of millet (pennisetum glaucum [Linn.]) husk filled high density polyethylene composites - Abba, Hammajam Alhaji (2014)
Millet husk (MH) is by product of cereal grain millet (p. glaucum) from mill. The main purpose of this research was to study the potential of this by product as filler for thermoplastic composites as an alternative to inorganic filler and other natural fibers.The chemical compositions of the fiber were 50.44 %, cellulose, 23.17 % hemicelluloses and 13.19 % lignin respectively. The fiber thermal properties were investigated by means of thermogravimetric analyzer (TGA) and thermal decomposition of the fiber was found to be stable at 245 °C. The moisture content was determined using oven-dry value analysis, thus indicated stability for the fiber-matrix interaction in millet husk-high density polyethylene (MH-HDPE) composites fabrication. Three different fiber sizes; 250 μm, 500 μm and 750 μm were pulverized in this study, consisting of 10 %, 20 % 30 % and 40 % by weight fiber loadings. The MH-HDPE composites were prepared by applications of internal mixer, accompanied by compression molding process. The mechanical properties; tensile, flexural and impact were tested using Instron universal testing machine. The morphologies of fractured surfaces were studied by using scanning electron microscope (SEM). Tensile strength decreases, while tensile modulus increased by increasing the millet fiber loading. The tensile strength of MH-HDPE composites were higher 19.2 % at 10 % fiber loading for 250 μm fiber sizes, 11 % at 10 % fiber loading for 500 μm fiber sizes and 9 % at 10 % fiber loading for 750 μm fiber sizes. While, the tensile modulus of MH-HDPE composites were higher 40 % at 40 % fiber loading for 250 μm fiber sizes, 35.2 % at 40 % fiber loading for 500 μm fiber sizes and 41.2 % at 40 % fiber loading for 750 μm fiber sizes. Flexural stress of the MH-HDPE composites were higher 37 % at 40 % fiber loading for 250 μm fiber sizes, 24.5 % at 20 % fiber loading for 500 μm fiber sizes and 32 % at 20 % fiber loading for 750 μm fiber sizes. while flexural modulus higher 64 % at 40 % loading for 250 μm fiber sizes, 58 % at 30 % fiber loading for 500 μm fiber sizes and 53 % at 40 % fiber loading for 750 μm fiber sizes. The impact strength of the MH-HDPE composites was slightly higher at 10 % fiber loading for all the fiber sizes. The reason why flexural and impact properties gave lower values for fiber loading above 10 % are possibly due to the fiber-to-fiber interaction, void and dispersion problems. Further, impact strength considerably decrease for all the fiber sizes as the fiber loadings increase compare to unfilled (100%) HDPE composites. Hence at 10% fiber loading, there was slight improvement in strength for 250 % μm fiber size. Thus, the composites tensile and flexural modulus increases as the fiber loading increase. The flexural strength increase up to 20 % fiber loadings, but decrease as loading increases. Tensile strength increase at 10 % fiber loading, but decrease as the fiber loadings increase above 10 % fiber loadings. While the impact strength decrease as the fiber loading increase for all the fiber sizes.